Women’s Traits In The Iraqi Satirical Television Show ‘State Of Melon’ A Paper Extracted from A Masters Thesis - Kadom, Nawara Ayad; AL Jubori, Irada Zaydan (ALBAHITH ALALAMI, 2022)
The research aims to know the traits or characteristics of woman in terms of her external appearance, motives for her behavior, feelings, mood and ability. It, moreover, seeks woman’s relationship with others as it is presented by the Iraqi satirical television show “ State of Melon “. The researcher adopted for that survey approach using the method of content analysis to study the research sample represented by “ State of Melon “ show which was exposed through the screen of a group of channels: “Hona Baghdad Satellite Channel, then Asia Satellite Channel, Dijla Satellite Channel, and UTV Satellite Channel.”For this, the researcher used Margaret Gallagher’s Model to analyze the image of woman in the Show episodes, which amounted to (132) episodes, divided into (the second season - and the pre-season episodes of the third - and the third season - and the fourth season - the fifth season). In the light of this study, the researcher reached a set of results, which are: 1.The woman appeared dependent in her relationship with others, in addition to being anxious and aggressive in her mood and feelings. 2.The woman image is considered among the hesitant and volatile characters of the group of competence and capacity characters on the show. 3. At the forefront of the motives for woman›s behavior in the «State of Melon» Show was that woman was driven by her feelings, while her outward appearance was dominated by rudeness.